Digital health technologies and the realization of sexual reproductive health and rights for adolescent girls in Uganda - Killander, Magnus (University of Pretoria, 2024)
Mini Dissertation (Mphil (Sexual Reproductive Health Rights in Africa))--University of Pretoria, 2023.